Impact of energy straggle on proton-induced single event upset test in a 65-nm SRAM cell - 叶兵 刘杰 王铁山 刘天奇 罗捷 王斌 殷亚楠 姬庆刚 胡培培 孙友梅 侯明东 (Chinese physics B, 2017)
This paper presents a simulation study of the impact of energy straggle on a proton-induced single event upset （SEU） test in a commercial 65-nm static random access memory cell. The simulation results indicate that the SEU cross sections for low energy protons are significantly underestimated due to the use of degraders in the SEU test. In contrast, using degraders in a high energy proton test may cause the overestimation of the SEU cross sections. The results are confirmed by the experimental data and the impact of energy straggle on the SEU cross section needs to be taken into account when conducting a proton-induced SEU test in a nanodevice using degraders.